(untitled) (International Journal of Agricultural Research, Innovation and Technology, 2014)
The health of urban forest communities not only depend on the government and nongovernmental organizations, but also strongly rely on local community stewardship. A study was carried out to assess community perceptions on the establishment of an urban forest plantation among urban residents in Dzivaresekwa, an urban area in Harare. Randomized systematic sampling was used to select 150 households and one resident per household was interviewed using a pretested questionnaire with both closed and open-ended questions. The objectives of the study were to determine how age and gender and employment status variables, were related to the urban residents perceptions towards establishment of a forest plantation in an urban area. Most females (58.3%) viewed the plantation as a threat while most men (51.7%) viewed the plantation as a recreational area. The highest proportion (61.9%) of the middle age group (21-40 years) perceived the plantation as a source of employment. There was a statistically significant relationship (p = 0.040) between gender and the general perception of establishing a forest plantation in the urban area. However, there was no statistically significant relationship (p = 0.203) between age groups and the perception of establishing a forest plantation in the urban area. It is concluded that the community had diverse perceptions on urban community forestry. DOI: http://dx.doi.org/10.3329/ijarit.v4i1.20973 Int. J. Agril. Res. Innov. & Tech. 4 (1): 16-23, June, 2014